Safety and efficacy of a feed additive consisting of a preparation of essential oils of thyme and star anise, and quillaja bark powder (BIOSTRONG® 510 all natural) for all poultry species (Delacon Biotechnik GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of a preparation consisting of essential oils of thyme and star anise, and quillaja bark powder (BIOSTRONG® 510 all natural) as a zootechnical feed additive (functional groups: digestibility enhancer; other zootechnical additives) for all poultry species. BIOSTRONG® 510 all natural is a preparation of partially microencapsulated essential oils, quillaja bark powder, dried herbs and dried spices. The additive contains estragole (up to ■■■■■. For short‐living animals, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) had no safety concerns when the additive is used at the recommended level of 150 mg/kg complete feed for chickens for fattening and other poultry species for fattening. For long‐living animals, the use of the additive was considered of concern owing to the presence of estragole. No safety concern would be expected for the consumer and the environment from the use of the additive at the recommended use level in feed. The Panel concluded that the additive is corrosive to the eyes but not irritant to skin. It may be a respiratory irritant or dermal or respiratory sensitiser. When handling the additive, exposure of unprotected users to estragole ■■■■■ may occur. Therefore, to reduce the risk, the exposure of the users should be minimised. The additive BIOSTRONG® 510 all natural was considered efficacious for chickens for fattening at the use level 150 mg/kg complete feed. This conclusion was extrapolated to all poultry species for fattening or reared for laying/breeding. ■■■■■